Hungry girl 200 under 200 just desserts : 200 recipes under 200 calories - Lillien, Lisa (St. Martin's Griffin, 2013)
"Calling all dessert fanatics: Get ready for an entire cookbook of decadent treats with under 200 calories each! Now, you can indulge and satisfy your sweet tooth with none of the guilt! Only Hungry Girl could create delicious guilt-free recipes like... Gooey German Chocolate Cake Mug (194 calories!) PB Cheesecake Chocolate Cupcakes (154 calories!) Strawberry Snowball Cupcakes (134 calories!) Roarin' Red Velvet Cake Pops (94 calories!) Black Forest Brownies (140 calories!) Banana Cream Cutie Pies (107 calories!) Freezy Cookies 'n Cream Whoopie Pie (164 calories!) Cuckoo for Cannoli Crunchers (107 calories!) Strawberry Shortcake Cream Fluff Cups (96 calories!) Berry-Good Tropical Trifle (189 calories!) Baked Caramel 'n Coconut Apples (140 calories!) This is the first-ever all-dessert cookbook from Hungry Girl, and it's sure to please sweets-obsessed Hungry Girl fans everywhere!"--